Are omentectomy and lymphadenectomy necessary in patients with apparently early-stage malignant ovarian germ cell tumors?. Issue 2 (23rd January 2019) - Qin, Beijiao; Xu, Wenyan; Li, Yanfang
Abstract : Objective: To evaluate the role of omentectomy and lymphadenectomy in the treatment of clinically apparent early-stage malignant ovarian germ cell tumors. Methods: We retrospectively reviewed 245 patients with malignant ovarian germ cell tumors (yolk sac tumor, dysgerminoma, and immature teratoma) and with clinically early-stage disease, who were treated at Sun Yat-sen University Cancer Center between January 1, 1970 and December 31, 2017. The survival of patients who underwent either omentectomy or lymphadenectomy, or both (omentectomy/lymphadenectomy group) was compared with that of patients who did not undergo omentectomy or lymphadenectomy (non-omentectomy/lymphadenectomy group). Results: Sixty patients were diagnosed with yolk sac tumor, 74 with dysgerminoma, and 111 with immature teratoma. Of these 245 patients, 216 patients had stage I disease, 28 patients had stage II, and 1 patient had stage IIIA. There were 190 patients who underwent omentectomy and/or lymphadenectomy and 55 patients in the non-omentectomy/lymphadenectomy group, respectively. In the omentectomy/lymphadenectomy group, 112 patients underwent both omentectomy and lymphadenectomy, 71 underwent omentectomy only, and 7 underwent lymphadenectomy only. Two hundred and fourteen of 245 patients (87.3%) received post-operative chemotherapy. Median follow-up was 73 months (range 1–388). The 10-year overall survival rates in the omentectomy/lymphadenectomy group and non-omentectomy/lymphadenectomy groups were 96.8% and 100%, respectively (p=0.340). Multivariate analysis evaluating all potential prognostic factors showed that omentectomy and lymphadenectomy are not prognostic factors for survival. Conclusions: Omentectomy and lymphadenectomy do not appear to improve survival and may be omitted in patients with clinically apparent early-stage malignant ovarian germ cell tumors.